Concurrent subglottic and carotid sheath haemangiomas in a paediatric patient – an extremely rare clinical entity. Issue 11 (22nd November 2022) - Dolan, Sean; Alatsatianos, Anton; McAllister, Kerrie; Kunanandam, Thushitha
Abstract: Multiple haemangiomas of the head and neck area have been reported sporadically in the literature. Concurrent subglottic and carotid sheath haemangiomas have not been reported before in the paediatric population. The authors present the case of a 13-week-old child admitted under the paediatric ENT team with stridor. Diagnostic micro-laryngoscopy identified a subglottic haemangioma as the cause of stridor and subsequent magnetic resonance imaging demonstrated an incidental 7 cm carotid sheath lesion extending from the skull base to the superior mediastinum. Subsequent biopsy confirmed a benign infantile haemangioma. To our knowledge, this is the first reported case of concurrent subglottic and carotid sheath infantile haemangiomas in a paediatric patient. Here we discuss the clinical features and management of infantile haemangioma.